Drawdown measures: Are they all the same? - Olaf Korn; Philipp M. Möller; Christian Schwehm (University of Cologne, Centre for Financial Research (CFR), 2019)
Over the years, a diverse range of drawdown measures has evolved to guide asset management. We show that almost all of these measures fit into a unified framework. This new framework simplifies the implementation of drawdown measures and improves understanding their similarities and differences. Conceptual differences between drawdown measures translate into different rankings of portfolios, which we document in a simulation study. Our research also shows that all drawdown measures can (to some degree) discriminate between skillful and unskillful portfolio managers, but differ in terms of accuracy. However, the ability to detect skill does not easily improve performance ratios where drawdown measures serve as the denominator. In conclusion, our study shows that the choice of an adequate drawdown measure is vital to the assessment of investments because different measures emphasize different aspects of risk.
Keywords: G11; 330; Asset Management; Drawdown; Risk Measures; Performance Measurement